1991
DOI: 10.1177/019874299101600207
|View full text |Cite
|
Sign up to set email alerts
|

Public School Services for Behaviorally Disordered Students: Program Practices in the 1980s

Abstract: In a previous article, a conceptual scheme for describing and evaluating programs in behavioral disorders was presented. Using instrumentation based on that conceptual scheme, 145 special education administrators in 27 states were surveyed about current educational practices in public school programs for children with behavioral disorders. Results of the survey are presented under four broad headings: student identification practices, service delivery, student exit procedures, and program evaluation practices.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In an earlier survey, we found that teachers of students with emotional and behavioral disorders were primarily responsible for developing and implementing nearly all aspects of the education program, including a suitable academic curriculum (Grosenick, George, George, & Lewis, 1991). Given the wide range of teachers' classroom responsibilities, we asked them to rate on a Likert scale the adequacy of time available for (a) developing curricula and (b) completing other forms of paperwork.…”
Section: Other Issues Discriminating Potential Leavers From Stayersmentioning
confidence: 99%
“…In an earlier survey, we found that teachers of students with emotional and behavioral disorders were primarily responsible for developing and implementing nearly all aspects of the education program, including a suitable academic curriculum (Grosenick, George, George, & Lewis, 1991). Given the wide range of teachers' classroom responsibilities, we asked them to rate on a Likert scale the adequacy of time available for (a) developing curricula and (b) completing other forms of paperwork.…”
Section: Other Issues Discriminating Potential Leavers From Stayersmentioning
confidence: 99%
“…Often, these behaviors are resistant to conventional methods of classroom management. When traditional strategies prove to be ineffective, it is common for schools to either apply more severe disciplinary procedures or place students in increasingly restrictive school programs (Grosenick, George, George, & Lewis, 1991). These alternatives, however, are This investigation was supported by Field-Initiated Research Grant H023C1012 from the U.S. Department of Education (Office ofSpecial Education Programs).…”
mentioning
confidence: 99%
“…Typical practice in schools for the 1-5% of students with the most complex emotional and behavioral needs is to move them to highly restrictive segregated settings with little interaction with the environments and instruction recommended for improved functioning (Grosenick et al 1991). Striving to move from this "identify and place" mentality to an intervention culture, SWPBS uses a public health multi-tiered model to conceptualize a school-wide prevention focus for all students (Kutash et al 2006).…”
Section: Multi-tiered Systems Of Support In Schoolsmentioning
confidence: 99%